2022
DOI: 10.1128/spectrum.01065-22
|View full text |Cite
|
Sign up to set email alerts
|

Blue Light-Dependent Pre-mRNA Splicing Controls Pigment Biosynthesis in the Mushroom Terana caerulea

Abstract: The regulation of natural product biosyntheses in mushrooms in response to environmental cues is poorly understood. We addressed this knowledge gap and chose the cobalt crust mushroom Terana caerulea as our model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 75 publications
(87 reference statements)
1
14
0
Order By: Relevance
“…The genome of H. rutilans CBS 490.95 was sequenced, yielding 34.8 Mbp of sequence data, distributed on 375 contigs. To bioinformatically browse the data for genes encoding tri-domain NRPS-like enzymes, the corA gene (GenBank: OM515349.1 [ 13 ]) of Terana caerulea served as a query. Two genetic loci, hereafter referred to as hapA1 and hapA2 , were identified that met the criteria: hapA1 is 3090 bp long, disrupted by three predicted introns and encodes a 106.8 kDa protein with 964 amino acids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The genome of H. rutilans CBS 490.95 was sequenced, yielding 34.8 Mbp of sequence data, distributed on 375 contigs. To bioinformatically browse the data for genes encoding tri-domain NRPS-like enzymes, the corA gene (GenBank: OM515349.1 [ 13 ]) of Terana caerulea served as a query. Two genetic loci, hereafter referred to as hapA1 and hapA2 , were identified that met the criteria: hapA1 is 3090 bp long, disrupted by three predicted introns and encodes a 106.8 kDa protein with 964 amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…2 ). The most recently characterized member of basidiomycete quinone synthetases is CorA [ 13 ]. It produces polyporic acid that feeds corticin biosynthesis in the Cobalt Crust Mushroom Terana caerulea .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Studies had shown that blue light-dependent pre-mRNA splicing controled pigment biosynthesis in the mushroom Terana caerulea. 55 One hour blue light irradiation everyday significantly reduced the number of spores and inhibit the growth of Penicillium italicum. 56 Red light irradiation under different conditions promoted the production of YP and RP and inhibited the production of OP and citrinin in M. purpureus M9.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the appropriate intensity of light and MF could promote the growth and metabolism of fungi 54 . Studies had shown that blue light‐dependent pre‐mRNA splicing controled pigment biosynthesis in the mushroom Terana caerulea 55 . One hour blue light irradiation everyday significantly reduced the number of spores and inhibit the growth of Penicillium italicum 56 .…”
Section: Discussionmentioning
confidence: 99%